Thermal and structural behavior of cold-formed steel frame wall under fire condition. (1st February 2022) - Samiee, Parisa; Esmaeili Niari, Shirin; Ghandi, Elham
Highlights: Investigation of the thermal and structural behavior of the LSF walls at high temperatures by numerical study. Conducting parametric study to investigate the effect of various parameters on the thermal and structural behavior of LSF wall. Calculation of temperature distribution and time–temperature profile of the wall component and fire-resistance rating (FRR) of the wall. Significant influence of sheathing on the fire-resistance rating of walls. Abstract: Light gauge Steel Frame (LSF) system, are extensively used in residential, commercial and industrial buildings. Its growing popularity in building construction industry is due to several advantages over other construction materials such as light weight, high strength and stiffness, uniform quality, ease of prefabrication and mass production, economy in transportation and handling. Fire safety of cold-formed steel structures has become more important since cold-formed thin-walled steel sections heat up quickly under fire condition (high section factor and high thermal conductivity) and present low fire resistance. LSF wall systems are used as primary load bearing structural members providing strength and stability in multi-story LSF buildings. Therefore a better understanding of the fire performance of LSF wall systems is required. The structural behavior of the LSF walls at high temperatures depends on the temperature distribution at the wall component and the mechanical property of cold-formed steel and other materials used in LSF walls at elevated temperatures. Also, the thermal performance of the LSF wall is influenced by its components, including the stud cross-section, stud size, sheathing, and insulation types and their thicknesses, and thermal properties of them. In this paper, a numerical study was undertaken using the finite element program ABAQUS. The structural finite element analysis were conducted under transient state condition using the time–temperature profiles of wall components obtained from the thermal analysis. The finite element thermal and structural models were first validated by comparing their results with the previous test results and then a parametric study was conducted with considering the effect of various parameters such as type of sheathing and its arrangement, stud web depth, stud flange width, and stud cross-section shape. The temperature distribution and time–temperature profile of the wall component and Fire-Resistance Rating (FRR) of the wall have been calculated. The results showed that sheathing is one of the most critical factors in fire resistance of walls and has a significant influence on the FRR of walls and increasing the stud depth affects the thermal and structural behavior of the LSF wall and leads to an increase in the FRR of the wall against fire. Also, increasing the stud flange width of LSF wall does not affect the thermal behavior and temperature distribution of the wall, but leads to an increase in the FRR of the wall against fire. The stud cross-section shape does not affect the temperature distribution in the cross-section but can affect the wall's behavior under fire conditions.